Estimation of unemployement in Malaysia using fourth-order taylor’s series method and fourthorder runge kutta method / Nur Batrisyia Suhaimi - Suhaimi, Nur Batrisyia (2021)
The number of unemployment increase and decrease in every month but the number always remains high. The data for unemployment in Malaysia can be search at Department of Statistic Malaysia (DOSM) online portal. For this research, mathematical modelling method are used to estimate the data collected from DOSM online portal which is the data of unemployed number in Malaysia. Data collected are from 2015 to 2020 by month. Mathematical modelling method that are used in this research to estimate the number of unemployment are Taylor’s series method and Runge-Kutta method where the degree order for both methods are fourth-order. The estimation value of fourth-order Taylor’s series method and fourth-order Runge-Kutta method are compared and analysed by using the error analysis. Comparison of error of both methods is to determine which method is more accurate, so that the method will be concluded as the best method for this research. Based on this study, fourth-order Runge-Kutta method is the best method as the method has least total value of error and more accurate. Hence, the number of unemployment in Malaysia for year 2021 to 2025 was estimated using fourth-order Runge-Kutta method.